Implications of changes in the Northern Hemisphere circulation for the detection of anthropogenic climate change - Gillett, N; Hegerl, G; Allen, M; Stott, P (2000)
The first principal component of Northern Hemisphere sea level pressure, known as the Arctic Oscillation (AO) index, has increased significantly in recent winters, and this change is associated with ~30% of Northern Hemisphere January-March warming. We examine the AO in a model used to detect anthropogenic influence on climate, and find that it exhibits no systematic trend in response to greenhouse gas, sulphate aerosol, or ozone forcing. To test the significance of this discrepancy for anthropogenic climate change detection, we include the spatio-temporal pattern of temperature change associated with the observed AO in the set of forcing-response 'fingerprints' used to account for observed changes, thus separating temperature change associated with the AO from a residual. We find that the detection of a global response to both anthropogenic greenhouse gases and sulphate aerosols is robust to this exclusion of AO-related warming.